Circulating Tumor DNA Detection in the Management of Anti-EGFR Therapy for Advanced Colorectal Cancer - Knebel, Franciele H.; Bettoni, Fabiana; da Fonseca, Leonardo G.; Camargo, Anamaria A.; Sabbaga, Jorge; Jardim, Denis L. (Frontiers in Oncology, 2019)
Background: Anti-EGFR antibodies are a standard care for advanced KRAS-wild type colorectal cancers. Circulating tumor DNA (ctDNA) monitoring during therapy can detect emergence of KRAS mutant clones and early resistance to therapy. Case Presentation: We describe a 61-years-old man presenting a metastatic and recurrent rectal cancer treated with different chemotherapy regimens. His tumor was KRAS wild-type based on tissue analysis and he was treated sequentially with cetuximab-based chemotherapy, chemotherapy alone and panitumumab-based chemotherapy. We performed sequential analysis of ctDNA using droplet digital PCR (ddPCR) and a commercial assay designed for the detection of frequent KRAS mutations during his clinical follow-up. Prior to the first cetuximab-based chemotherapy ctDNA analysis demonstrated an absence of KRAS mutations. Emergence of KRAS mutations in ctDNA occurred 3 months after treatment initiation and preceded clinical and imaging progression in about 2 months. Fractional abundance of KRAS mutation rapidly increased to 70.7% immediately before a chemotherapy alone regimen was initiated. Interestingly, KRAS mutation abundance decreased significantly during the first two months of chemotherapy, reaching a fractional abundance of 3.0%, despite minimal clinical benefit with this therapy. Re-challenge with a different anti-EGFR antibody was attempted as later line, but high levels of KRAS mutations in ctDNA before therapy correlated with an absence of clinical benefit. Conclusions: The monitoring of resistance mutations in KRAS using ctDNA during the treatment of KRAS wild-type advanced colorectal cancers can detect the emergence of resistant clones prior to clinical progression. Dynamics of resistant clones may alter during periods on and off anti-EGFR antibodies, detecting window of opportunities for a re-challenge with these therapies.